PERMASALAHAN STUNTING PADA ANAK DI KABUPATEN YANG ADA DI JAWA BARAT - Erlita Firdanti; Zahrah Anastya; Nabilah Khonsa; Raja Maulana (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Stunting is one of the many health problems in Indonesia. This study aims to determine the condition of stunting. Stunting in districts in West Java as well as efforts to prevent stunting problems. This study uses the method of literature review or literature review. The results of this study indicate that in 18 districts in West Java, in 2019 the percentage of stunting in Pangandaran Regency was at 21.67%. Meanwhile, in 2020 Tasikmalaya Regency has the highest stunting percentage, which is 18.97%. There are efforts to socialize nutritional information literacy, training for posyandu cadres, counseling and education on balanced nutrition, Nutri Zinc rice food, PAMSIMAS program, Bandung Tanginas program, milk drinking movement, Si Keren Halo Cinta program, TORASTING, Kissing program, Team Agile, Teeth Setting program Gold, Stunting Consultation, and providing additional food for mothers and toddlers are efforts made to prevent stunting